2021
DOI: 10.3892/br.2021.1420
|View full text |Cite
|
Sign up to set email alerts
|

Leptin and the GA genotype of rs2167270 of the LEP gene increase the risk of prediabetes

Abstract: Prediabetes is a precursor stage that frequently develops to definitive type 2 diabetes mellitus (T2DM). Therefore, identifying individuals with prediabetes can allow for early intervention measures that delay or prevent disease progression to T2DM. Several biochemical changes appear to be associated with prediabetes, including an increase in the serum levels of leptin. In Jordan, this association has not been previously investigated. In the present study, the serum levels of leptin were measured in 122 predia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 33 publications
0
3
0
Order By: Relevance
“…In a study on common variants in the leptin gene, researchers showed an association of the AA genotype of the rs7799039 variant with the development of obesity in the population of South India [ 136 ]. The A allele of rs2167270 significantly correlates with an elevated risk of prediabetes in Jordan and in the population of South India [ 137 , 138 , 139 ]. Rs6966536 (allele G) of the LEP gene has been implicated in the development of obesity in a South African population [ 140 ].…”
Section: Resultsmentioning
confidence: 99%
“…In a study on common variants in the leptin gene, researchers showed an association of the AA genotype of the rs7799039 variant with the development of obesity in the population of South India [ 136 ]. The A allele of rs2167270 significantly correlates with an elevated risk of prediabetes in Jordan and in the population of South India [ 137 , 138 , 139 ]. Rs6966536 (allele G) of the LEP gene has been implicated in the development of obesity in a South African population [ 140 ].…”
Section: Resultsmentioning
confidence: 99%
“…Instead, the A allele and GG genotype of rs2167270 were more prevalent among atopic dermatitis patients (13). Aljanabi et al (19) also showed that both the A allele and GA genotype of rs2167270 of the leptin gene are highly associated with the prevalence of prediabetes (P < 0.05). The different genotypes of SNP rs2167270 are thought to be associated with higher or lower expression of the LEP gene (20).…”
Section: Discussionmentioning
confidence: 99%
“…It was also found that patients with poor glycemic control have lower serum leptin levels. Interestingly, our group showed that Jordanian patients who have prediabetes, a state characterized by elevated levels of serum leptin, are more likely to carry the GA genotype of rs2167270 [ 21 ]. Taken together, it could be hypothesized that in Jordan, the GA genotype of rs2167270 is linked with metabolic conditions associated with elevated levels of serum leptin.…”
Section: Discussionmentioning
confidence: 99%
“…Leptin is a hormone-like adipokine secreted by adipose tissue cells [ 21 , 22 ]. Inactivating mutations in the gene that codes for the leptin hormone ( LEP ) are linked with obesity in humans [ 23 ] and in rodent models [ 24 ].…”
Section: Introductionmentioning
confidence: 99%